Clinical Spectrum and Genetic Diagnosis of 54 Consecutive Patients Aged 0–25 with Bilateral Cataracts - Suzannah Bell (Genes, 2021)
Childhood cataract affects 2.5–3.5 per 10,000 children in the UK, with a genetic mutation identified in 50–90% of bilateral cases. However, cataracts can also manifest in adolescence and early adulthood in isolation, as part of a complex ocular phenotype or with systemic features making accurate diagnosis more challenging. We investigate our real-world experience through a retrospective review of consecutive bilateral cataract patients (0–25 years) presenting to the ocular genetics service at Moorfields Eye Hospital between 2017 and 2020. Fifty-four patients from 44 unrelated families were identified, with a median age of 13.5 years (range 1 to 68 years) and a median age at diagnosis of 43.9 months IQR (1.7–140.3 months); 40.7% were female and 46.3% were Caucasian. Overall, 37 patients from 27 families (61.4%) were genetically solved (50%) or likely solved (additional 11.4%), with 26 disease-causing variants (8 were novel) in 21 genes; the most common were crystallin genes, in 8 (29.6%) families, with half occurring in the CRYBB2 gene. There was no significant difference in the molecular diagnostic rates between sporadic and familial inheritance (P = 0.287). Associated clinical diagnoses were retinal dystrophies in five (18.5%) and aniridia in three (11.1%) families. Bilateral cataracts were the presenting feature in 27.3% (6/22) of either complex or syndromic cases, and isolated cataract patients were 11.5 years younger (rank-sum Z = 3.668, P = 0.0002). Prompt genetic investigation with comprehensive panel testing can aid with diagnosis and optimise management of cataract patients.